(untitled) (Progressive Agriculture, 2021)
The present study was conducted to determine the early sex in turkeys by observation of the differences in body weight between male and female birds. A total of 30-day old black color unsexed poults having almost similar body weight at hatching were considered for the experimentation and housed at the Poultry Farm of Bangladesh Agricultural University, Mymensingh-2202, Bangladesh. All birds were reared up to 12 weeks of age under intensive management with supplementation of commercial broiler starter and grower feeds. Birds were reared under similar management conditions. Significantly higher (p<0.01) body weight was attained in male poults (104g/bird) than the female (90g/bird) at the end of 1st week of age. Similarly, at the end of 2nd week of age higher (p<0.01) body weight attained by male poults (198.31g/bird) than the female (162.13g/bird). At the end of 3rd weeks of age male poults attained higher (p<0.01) body weight (307.23g/bird) than the female (251.33g/bird). After 4 weeks of rearing, male turkeys attained significantly higher (p<0.01) live body weight (424.46g/bird) than the female turkeys (347.87g/bird). The weekly average body weight gains of male and female birds were 94.18g/bird and 76.5g/bird, respectively. Thus, the male and female birds were successfully identified on the basis of differences in their body weight. Weekly feed intake for both the male and female birds was also increased with their age. Up to 4 weeks of age, both the male and female poults consumed same amount of feed (753.46g/bird). The FCR of male and female poults differed non-significantly in 1st, 3rd and 4th week. On the contrary, in 2nd week of age the FCR of male poults (1.60) was significantly lower (p<0.01) than female (2.11). Survivability was 100% up to 4th week of age irrespective of sex of the poults. The birds were reared up to 12 weeks of age until to confirm their sex by observation of the phenotypic appearance. Results of the phenotypic observation of male and female birds correspondence hundred percent accuracy with the results obtained in body weight based differences between male and female birds. It is therefore concluded that farmers can identify male or female poults as early as first week of age on the basis of body weight differences. Progressive Agriculture 31 (3): 218-226, 2020